Understanding the Socio-Cultural Determinants of Health-Seeking Behaviour and Health Information Trust Among Women At-Risk for Female Genital Schistosomiasis in Ghana - Patel, Kruti (Université d'Ottawa / University of Ottawa, 2022)
Female genital schistosomiasis (FGS) is a chronic manifestation of schistosomiasis, a waterborne parasitic infection, and is estimated to impact 56 million women predominantly in Sub-Saharan Africa. Currently, there is scarce literature on FGS and related health-seeking behaviour (HSB) among at-risk women. The objective of this mixed-method study is to understand the socio-cultural determinants of HSB and the health information trust networks for women at-risk of FGS in Ghana. A cross-sectional survey and twelve focus group discussions (FGDs) were conducted in the North Tongu and Weija Districts of Ghana. A total of 863 cross-sectional surveys and 12 FGDs were administered in both districts. There was an overall lack of awareness of FGS among adult women (38.9%). Only 48.8% of women reported HSB from the 86 women who choose to talk about their FGS-related symptoms. HSB was significantly associated with monthly steady income (p-value: 0.036) and level of education (p-value: 0.15,0.27), when controlling for age group and source of trusted health information. Some of the determining themes for HSB included: environmental and systemic context, shared norms, and apprehensions. Active and passive health information-seeking behaviour also emerged through the FGDs. Taking a mixed-method approach allowed for the appraisal of both methodologies and provided validity to the results. The lack of awareness of FGS indicates the need for tailored health information campaigns in endemic communities. More research is required on the FGS diagnostic and treatment capabilities of health facilities to understand their impact on HSB of women. This investigation finds that social, environmental, and cultural determinants are involved in the HSB of women at-risk for FGS, in North Tongu and Weija.
Keywords: Global Health; Women's Health; Health-Seeking Behaviour; Neglected Tropical Diseases; Mixed Methods